A thumb on the scale: measures short of a prohibition to combat hate speech. Issue 1 (2nd January 2022) - Rowbottom, Jacob
ABSTRACT: While debates on hate speech often focus on the case for banning certain types of expression, this article will focus on less restrictive alternatives. The article will consider the denial of a benefit normally granted to speakers, media regulations and government sponsored speech to counter messages of hate. Such measures, it is argued, are more proportionate than an outright ban and do not exclude any particular viewpoints from political debate. However, such measures also depart from expectations of even-handedness from public bodies in relation to political viewpoints. With these factors in mind, the discussion explores the potential for some types of speech to occupy a grey area, in which messages of hate or extremism do not meet the threshold for prohibition but are still subject to viewpoint-based treatment that would not normally be compatible with freedom of expression.